Culture or oppression? - Liu, Chu-Li (Socialno delo, 2016)
Feminist theory is an important sociological theory that is very often used in social work research focusing on inequalities, power relations and social work gender analysis. Informed by feminist thoughts, domestic violence prevention system was first initiated in 1980's and the lens of misuse/abuse power is emphasized; legal aids, provisions of resources such as protection orders, shelters, etc. are central to the work. In contrast to the traditional view that domestic violence is a private matter, the goal is to indicate that domestic violence is a matter that the State needs to intervene in, take the blame off the victims and place the responsibility on the abusers. Research pointed out that survivors who were reported to the system experienced fragmented services or services that did not meet their needs, and thus it resulted in survivors withdrawing from the helping process, so the problems still occur in their lives on a regular basis. This paper uses examples of women in Taiwan with mental health problems who survived their male partners' violence and were trapped in multiple interlocking vulnerable situations, to demonstrate how various oppressive factors work in survivors' context that stigmatized and constrained survivors. The analysis of vignettes indicated that women with mental health problems who survived their male partners' violence, face many obstacles that put them in vulnerable situations, including female gender norms developed from patriarchal values, coping strategies sanctioned by patriarchal and collective social contexts, and social exclusion developed from discrimination towards mental health problems. Therefore ignoring these obstacles, legal aids and providing shelters are limited. By analyzing interlocking vulnerable factors in survivors' context, it emphasizes the importance of a legal perspective as well as a comprehensive analysis of vulnerable factors in understanding survivors in inferior status. Implications for social work practice are addressed.
Keywords: feminist theory; feministična teorija; Taiwanese culture; tajvanska kultura; domestic violence; nasilje v družini; male perpetrators; storilci; sexual abuse; spolna zloraba